HOLOGRAPHIC EDUCATIONAL TECHNOLOGIES: DEVELOPMENT OF STUDENT ACTIVITY BASED ON A COGNITIVE APPROACH (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article highlights the scientific and theoretical foundations of the application of holographic technologies in the education system, their influence on the cognitive activity of students, and their significance in increasing learning motivation. Based on the cognitive approach, the possibilities of holographic technologies in activating student activity, methodological directions for their integration into the educational process were analyzed. Also, the creation of a holographic educational environment based on innovative pedagogical practices and its performance indicators are discussed.